Stimulating the spirit of neighbourliness among ethnicities in residential areas through urban cultural landscapes - Aziz, Nurul Aqilah; Ismail, Nor Atiah; Mohd Yunus, Mohd Yazid (Scottish Group, 2013)
This paper aims to look the potential of urban cultural landscapes to stimulate the spirit of neighbourliness among ethnicities in residential areas. The contribution of cultural landscapes in urban residential areas is not well established as one of the ways to enhance the physical character of residential areas because these greens are mainly perceived as being behind the times in design, outdated, old-fashioned and not being relevant in today’s technological world. In order to bridge this gap, this qualitative research adopted a focus group discussion (FGD) in the data process to capture the views of professional towards the cultural landscape as medium to stimulate neighbourhood values among residents of mixed ethnicities. The findings of this research affirm that urban cultural landscapes embedded high values and potential be used as elements to address the important issues pertaining to ethnicity and culture. At the same time, an urban cultural landscape helps to stimulate the feeling of neighbourliness although it is not well appreciated by the professionals and local authorities.